Moosense pedometer activity and periestrual hormone profile in relation to oestrus in crossbred cattle - KERKETTA, S; MOHANTY, T K; BHAKAT, M; KUMARESAN, A; BAITHALU, R; GUPTA, R; MOHANTY, A K; ABDULLAH, M; KAR, S; RAO, V; FAHIM, A (The Indian Journal of Animal Sciences, 2020)
The objective of the study was to establish the characteristics of pedometer activity in crossbred cows (20) and to determine the relationships between the pedometer activity and the serum concentrations of periestrual hormones. Animals in oestrus were detected by trained personnel based on oestrus behaviour by visual observation twice daily. Further oestrus was detected by pedometer activity and it was confirmed by serum progesterone and estradiol concentration. Individual animal daily activity data were collected and transformed into hourly activity in Excel sheet and arranged for statistical analysis. The relationship of pedometer activity with E2, E2: P4 and progesterone level on the day of oestrus was determined. Pearson correlation analysis was performed using the statistical package SPSS (SPSS Inc. USA). Activity count per hour (ACPH) increased from 248.51±22.46, 312.51±37.16, 323.52±49.24 and 423.42±47.77 from -3 day, -2 day and -1 day of proestrus, respectively to estrus day. After estrus, the activity decreased from 313.76±46.62 and 271.36±36.06 on the 1st day and 2nd day of metestrus, respectively. A similar trend was observed for serum E2 and E2: P4 which increased from 3 days before estrus to reach a peak level on the day of estrus (31.40±2.34 pg/ml) and declined after that to the basal level (2 pg/ml) after estrus. Contrary to this, P4 concentration showed a decreasing trend from –3 day proestrus to estrus (0.46±0.05) and then a gradual increase after estrus day. ACPH showed positive correlation with estradiol concentrations (r = 0.34; P = 0.0779) and E2:P4 ratio (r=0.50; P=2.077) but, negative correlation with progesterone concentration on day of oestrus (r=–0.73; P=2.74). In conclusion, our results suggested that the concentration of E2, E2:P4 ratio and P4 concentration during proestrus and on the day of estrus are the important factors contributing the behavioral manifestation of estrus in terms of ACPH in crossbred cows.